Factors influencing oilseed growers for enrolling as members of Karnataka Co-operative Oilseed Growers Federation Limited, Raichur Regional Union, Karnataka: FACTORS INFLUENCING OILSEED GROWERS FOR ENROLLING AS MEMBERS OF KOF, KARNATAKA - R S BHAWAR,; SURESH S PATIL,; G M HIREMATH, (Journal of Oilseeds Research, 2014)
The study was conducted purposively in the selected organization Karnataka Co-operative Oilseed Growers Federation Limited (KOF) and factors influencing on enrolling as member of KOF was judged by selecting top three Oilseed Growers Co-operative Societies (OGCS) from Raichur Regional Union (RRU) based on highest volume of business. From selected OGCS 45 members and 45 non members were selected to collect primary data. The data on primary source were analysed using Simple Ranking and Garret analysis. Factors influencing majority of respondents for enrolling as members of society were hope of reducing market risk (mean score 57.82) and no commission charge (mean score 53.31). Further majority of non-members had not registered in the society due to non availability of credit facility from society (mean score 55.77), personal relation built with commission agents over the year (mean score 54.31) and indebtedness to commission agent (51.71) as opined by non-member respondents.